Current developments in the regulation of direct-to-consumer genetic testing in Europe. (June 2015) - Kalokairinou, Louiza; Howard, Heidi C.; Borry, Pascal
Over the past years, direct-to-consumer (DTC) genetic testing has provoked controversy regarding its still questionable risks and benefits. The safety and performance of such devices, when entering the European market, are currently regulated by the Directive 98/79 EC of the European Parliament and of the Council on in vitro diagnostic medical devices. In September 2012, a new Regulation was proposed to replace this Directive, and the legislative process is still ongoing. This article presents the main points of the European Commission's proposal for the new Regulation and the subsequent amendments voted by the European Parliament, aiming to evaluate the potential contribution of the proposal for a more effective regulation of DTC genetic testing in Europe. In this regard, the proposal seems to enhance the current regulatory framework by further elucidating the scope of the Regulation and by establishing a risk-based classification system that guarantees increased pre-market scrutiny of the tests. Furthermore, the proposal attempts to establish higher safety and performance requirements and to enhance transparency. In addition, the European Parliament introduced amendments according to which appropriate genetic counselling is required in the context of genetic tests, and such tests are classified as prescription only, banning, at the same time, their DTC advertising. These developments have already provoked controversy among stakeholders and, if eventually adopted, they may lead to a radical change in the European DTC genetic testing landscape. In this light, the political decisions that will be taken imminently will be determinant.